Investigating Investigating the Use of Java-English Accent In The EFL Class - Febriana Aminatul Khusna; Lilia Indriani (Universitas Musamus Merauke, 2021)
English is an international language and its status in Indonesia as a foreign language. In learning English the learner must understand the usage of grammar, pronunciation of words, function of using words, etc. Pronunciation of words is one part that can not be separated from learning a language. In English language, the pronunciation of the word is included in the accent part that is used. At Tidar University, Central Java nearly 80 present of students comes from the Java area and uses Javanese accents. In other words, for those who are studying English, they have to adjust the use of accents when they speak English. This research is related to the accents used by students of English education study programs, universities in the TPTEFL class (theory and principle in teaching English as foreign language). Descriptive qualitative methods with data analysis using comparison and contrast or Received Pronunciation (RP) were used in this study. As a result, there were students whose pronunciation of English sounds was not optimal and tended to mix with Javanese accents. In this case, there are five voice-shifting speakers. Bilabial, interdental, velar, alveolar and glottal are the sounds that come out in this discussion.